PENEGAKAN HUKUM PENIPUAN DENGAN MODUS ONLINE SHOP MELALUI BLACKBERRY MESSENGER BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK OLEH PENYIDIK DITRESKRIMSUS KEPOLISIAN DAERAH SUMATERA UTARA - Obby Michael Angelo; Erdianto '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Technology development is one of factor which might bring about crime and the crime itself has been appearing since the beginning of time, present or even in the future. This case influences kind of crime which is varies and the technology this time becomes backsword, because beside providing contribution in improving prosperity, advancing human civilization and being an effective means of deed againts the law as well. By having technology, it can ease a criminal does his crime. Technology development in telecommunication and information side particularly, which is sweeping the world today, it can’t be avoided. The research result brings three main ideas which can be concluded. First, the investigation towards Criminal Fraud via Blacberry Messenger in Kepolisian Ditreskrimsus Juridictions, North Sumatera regional hasn’t done complete yet, perfectly. This can be seen from the case which hasn’t be revealed yet. The second one was the problems faced during the investigation of Online Shop criminal fraud via Blackberry Messenger are inadequate number of personnel, falicilities and infrastructure, including the low participatoion of community. The thrid one was the effort were used to solve investigations’ problems of criminal fraud via Blackberry Messenger by trying to improve the number of personnel and increase insight and knowledge about material offense as well. The discipline and dedication in doing assignment, especially the investigation itself. Key Words: Law Enforcement - Online Shop Fraud - Blackberry Messenger